E. coli lipopolysaccharide decreases the expression of proteins of tight junctions in the jejunum of weaning piglets / lipopolisacárido de e. coli disminuye la expresión de proteínas de uniones apretadas en yeyuno de lechones posdestete (2014)
Abstract. In order to assess the effect of the addition of E. coli lipopolysaccharide (LPS) on the expression of tight junction proteins in the jejunum of weaned piglets (the animals were weaned at 21-days-old), 64 piglets were slaughtered at 1, 5, 7 and 10 days postweanig and complete extraction of jejunum was carried out in order to evaluate the molecular expression of Claudine 3 (C3), Claudine 4 (C4), and Zonula Ocludens-1 (ZO-1). To induce intestinal inflammation, animals were fed a basal dietsupplemented with four levels of E. coli LPS (0, 0.3, 0.5, and 1.0 μg mg-1 of feed). The statistical design consisted of randomized blocks in a 4X4 factorial arrangement (four LPS concentrations and four post-weaning periods). A decrease was observed (P and lt;0.01) in the expression of C3, C4, and ZO-1 in the animals that were fed the diet with the highest LPS-inclusion level. LPS contributes to the appearance of anatomical and intestinal functional disorders which are denoted by a decrease in the molecular expression ofproteins from the intestinal barrier. This, in turn, is associated with an indiscriminate paracellular transport of molecules, microorganisms, and toxic compounds into the circulatory system. This results in post-weaning diarrhea and a decrease in the productive efficiency of piglets. / Resumen. Con el objetivo de evaluar el efecto de la adición de lipopolisacárido LPS de E. coli sobre la expresión de proteínas de las uniones apretadas en yeyuno de lechones destetos, se sacrificaron 64 lechones escalonadamente los días 1 (21 días de edad, día del destete), 5, 7 y 10 posdestete, y se les extrajo completamente el yeyuno para la evaluación de la expresión molecular de Claudina 3 (C3), Claudina 4 (C4), y Zonula Ocludens-1 (ZO-1). Para inducir la inflamación intestinal los animales fueron alimentados con una dieta basal, adicionada con cuatro niveles de LPS de E. coli (0; 0,3; 0,5 y 1,0 μg mg-1 de alimento). El diseño estadístico utilizado fue de bloques al azar en arreglo factorial de 4X4 (cuatro concentraciones de LPS en cuatro tiempos posdestete). Se observó la disminución (P and lt;0,01) en la expresión de C3, C4 y ZO-1 en los animales que consumieron la dieta con mayor nivel de inclusión de LPS. El LPS contribuye a desordenes anatómicos y funcionales a nivel intestinal, representados por la disminución en la expresión molecular de proteínas de la barrera intestinal, lo que está asociado al transporte paracelular indiscriminado de moléculas, microorganismos y compuestos tóxicos hacia la circulación sistémica. Todo lo anterior conlleva la presentación de diarreas posdestete y a la disminución en la eficiencia productiva de los lechones.